PENDIDIKAN AMAR MA'RUF NAHI MUNKAR DALAM MEWUJUDKAN KEPEDULIAN SOSIAL - Dian Sri Astuti; Jumari Jumari (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2019)
Amar Ma'ruf Nahi Mungkar Education is an effort made by someone (educator) towards (students) to achieve maximum and positive development. Amar Ma'uf Nahi Mungkar's Law fard ain if one person knows and fardhu kifayah if some people know it. With the phenomenology model and descriptive qualitative writing approach, this research was conducted by interviewing, observing, and documenting studies in data collection and descriptive technical analysis with data reduction procedures, data display and verification / conclusion drawing. Social care is an attitude and action that always wants to help other people and people in need. Changing kemunkararan through several ways, namely by changing with the hand intended for the leader, for example if the child does not perform the prayer then the person who knows especially the parents must remind. If the risk is dangerous then it is only obligatory to deny with the heart such as murder, and theft that is in Denanyar Utara Village Denanyar Jombang. And carry out some positive activities that educate to do good, public recitation and those related to religious activities to educate someone in forming actions that are with the religious shari'a in Denanyar Utara Village Denanyar JombangKeywords: Amar Ma'ruf Nahi Munkar Education in Realizing Social Concer